PERENCANAAN PANEN AIR HUJAN SEBAGAI SUMBER AIR ALTERNATIF PADA KAMPUS UNIVERSITAS DIPONEGORO - Faisal Nurrohman; Satria Waskita Eka Paksi; Sri Sangkawati; Sugiyanto Sugiyanto (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2015)
The design of rainwater harvesting is planned for alternative water source in UNDIP area and hopefully it can reduce the use of groundwater as the main source water to fill the demand of water in UNDIP area. The use of groundwater to fill the water demand in UNDIP campus for years 2014/2015 of 2,23 lt/dt it more than the optimum discharge are allowable to take the water wells is equal to 0,2-1 lt/dt. Based on that the planning of the rainwater harvesting building is made of with a volume of 245 m3 with a dimensions of 7m x 7m x 5m and dimensions of infiltration wells with a diameter of 1,5 and depth of 3m. Planning of the rain water harvesting in the UNDIP area the cost of Rp 275.465.000 with the process of work for 29 days.